Information Model for Monitoring the Development of the University - Suleimenova, Laura; Rakhmetullina, Saule; Denissova, Natalya; Krak, Iurii; Aitmukhanbetova, Elvira (International Journal of Computing, 2021)
Higher education institutions are becoming increasingly complex and self-developing systems. Monitoring the activities of such systems requires a special approach and includes three main elements, that is, external monitoring, independent evaluation and internal monitoring. In the framework of this article, the main task of monitoring is the analysis and disclosure of internal patterns, causes and trends of the development processes of a university. In these conditions, the need to move to a broader model for solving and reducing complexity based on information and knowledge is revealed. The model reduces the uncertainty of the environment and thus provides more effective decision-making. The monitoring model includes changes in the strategic planning process that are consistent with the characteristics of the new organizational model. Ontologies, as a theory of content, which allow formalizing processes and knowledge, are a key element in this context.